Employment Reallocation over the Business Cycle: Evidence from Danish Data - Antoine Bertheau; Henning Bunzel; Rune Majlund Vejlin (Institute of Labor Economics (IZA), 2020)
We present new evidence on how employment growth varies across firm types (size, productivity, and wage) and over the business cycle using Danish data covering almost 30 years. We decompose net employment growth into two recruitment margins: net hirings from/to employment (poaching) and net hirings from nonemployment. High-productivity firms are the most growing firms due to poaching. High wage firms poach almost as many workers, but shed an almost equal amount to non-employment. Large firms do not poach workers from smaller firms. In terms of employment cyclicality, we find that low-productive and low-wage firms shed proportionally more jobs in recessions. We relate our findings to recent models of employment fluctuations that jointly analyze worker and firm dynamics.
Keywords: E24; E32; J63; 330; worker flows; firm heterogeneity; matched employer-employee data; business cycle; equilibrium search models